2016
DOI: 10.1016/j.jfludis.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety disorders among children who stutter

Abstract: ANXIETY DISORDERS AMONG STUTTERING CHILDREN 2 Highlights Stuttering is a speech disorder that hampers communication in social situations  Roughly 22-60% of adults who stutter meet criteria for social anxiety disorder  No studies have evaluated the rate of anxiety disorders among stuttering children  Stuttering children demonstrated a significantly higher rate of anxiety disorders  Of note, 24% of stuttering children met criteria for social anxiety disorder AbstractPurpose: Stuttering during adulthood is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 66 publications
3
76
2
2
Order By: Relevance
“…Prospective studies also need to compare the results obtained with those from controls. Moreover, a recent study reported the need to utilize scales measuring anxiety levels that are specific to stuttering (28) . It is also recommended that a qualitative methodology be used in future studies in order to explore the resilience, perceived social support and anxiety levels of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies also need to compare the results obtained with those from controls. Moreover, a recent study reported the need to utilize scales measuring anxiety levels that are specific to stuttering (28) . It is also recommended that a qualitative methodology be used in future studies in order to explore the resilience, perceived social support and anxiety levels of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence now that mental health problems, notably social anxiety disorder, are present with children who stutter in the age range 7-12 years (Iverach et al 2016). According to that report, 24% of the stuttering children had social anxiety disorder compared with 5% of control children.…”
Section: Avoiding Chronic Stuttering With Early Interventionmentioning
confidence: 99%
“…In the only study to evaluate the prevalence of anxiety disorders among adults who stutter and non-stuttering controls using a structured diagnostic interview, 22% of adults seeking treatment for stuttering met criteria for social anxiety disorder compared to only 1.2% of non-stuttering controls from the general community (Iverach, O'Brian, et al, 2009). Whilst it was initially thought that these findings might only apply to adults who stutter, recent evidence suggests that social anxiety disorder may also be prevalent among school-age children who stutter (Iverach, Jones, et al, 2016). In particular, 24% of school-age children (7−12 years) seeking treatment for stuttering met criteria for social anxiety disorder, compared to only 4% of non-stuttering control children (Iverach, Jones et al, 2016).…”
Section: Stuttering and Social Anxiety Disordermentioning
confidence: 99%